Penguatan Numerasi dan Literasi Sains melalui Implementasi Projek Penguatan Profil Pelajar Pancasila berbasis STEM di SD Inklusi Kabupaten Sidoarjo - Sari, Yurizka Melia; Feriyanto, Feriyanto; Minarsih, Ni Made Marlin; Roqobih, Fikky Dian; Haq, Muhammad Dani Izzul (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
This community service aims to improve several aspects of education at SD Negeri Wonocolo 1, especially literacy and numeracy. Through strengthening numeracy and science literacy, it is hoped that students will not only be able to read and count, but also understand scientific concepts in everyday life. Another objective of this PKM is to utilize school land through the implementation of the STEM-based P5 Project. The PKM implementation method is the preparation stage, implementation stage, evaluation stage and program sustainability. This approach aims to improve teachers' abilities in implementing P5 teaching modules that integrate numeracy and science literacy using the school context through the STEM platform. The results of this community service are the formation of a community of practitioners between the principal and partner teachers, this community is able to share knowledge and discuss learning tools that are relevant to numeracy and science literacy, and facilitate active participation in STEM projects at school. Furthermore, there is an increase in teacher skills in the aspects of numeracy and science literacy based on STEM by ≥ 70% based on pre-test and post-test evaluations after training. The compilation of 3 P5 teaching modules covering the dimensions of creativity, independence, mutual cooperation, and global diversity, implemented in the context of STEM with the theme of Sustainable Development Goals, and the topic of Land Ecosystems (life on land), which resulted in three P5 teaching modules according to phases A, B, and C of the independent curriculum that are relevant for SDN Wonocolo 1.